Integrasi Zachman Framework dan TOGAF ADM - Pramudita, Rully; Safitri, Nadya (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System; Vol 1 No 2 (2017): INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS (Juni 2017), 2017)
Abstrak: Zachman framework merupakan salah satu framework arsitektur enterprise yang banyak digunakan, namun framework ini belum memiliki metodologi khusus dalam penerapannya. Selain Zachman framework ada juga The Open Group Architecture Framework Kata kunci: TOGAF ADM, Sistem Informasi Enterprise, Zachman framework Abstract: Zachman framework is one of the enterprise architecture framework that is widely used, but this framework does not yet have the specific methodology in its application. In addition to the Zachman framework there is also The Open Group Architecture Framework Keywords: Enterprise Information System, TOGAF ADM, Zachman framework